Bus Detection System for Blind People using GSM Technology - E. Govinda Kumar, K. L. Divyaprabhu, M.A. Rangini, S. Vignesh, N.B. Shyam Narendran (International Journal of Advanced Science and Technology, 2020)
An identification of a close atmosphere conditions are the major challenge of any visually impaired person. Visually impaired person is reaching their destination using the conventional methods such as guide cans, talking sign, transportation etc. In this work, wireless sensor networks are used for purpose of easy navigation of visually impaired persons. The main purpose of this work is to simplicity the traveling and movement of blind people using GSM technology. This method deals about the announcement of an arrived bus to the blind people. The results are confirmed that, performance of prototype system is operated in terms of safety and system functionality.